What is the range of this function?(6,-8)
(8,-3)
(10,5)
(12,7)


A. (-8, -3, 5, 6, 7, 8, 10, 12)
B. (-8, -3, 5, 7)
C. (-3, 7, 8, 12)
D. (6, 8, 10, 12)
What is the range of this function? (6,-8) (8,-3) (10,5) - 1

Answers

Answer 1
Answer:

Answer:

Step-by-step explanation:

(-8,-3,5,7) is the answer


Related Questions

A certain liquid has a density of 2.67 g/cm3. 30.5 mL of this liquid would have a mass of ________ Kg. 0.0114 11.4 0.0814 0.0875 81.4
The legs of a right triangle measure 5√2 cm and 4√2 cm. Find the area.
A fruit stand has to decide what to charge for their produce. They need \$5.30$5.30dollar sign, 5, point, 30 for 111 apple and 111 orange. They also need \$7.30$7.30dollar sign, 7, point, 30 for 111 apple and 222 oranges. We put this information into a system of linear equations.
I have no idea how to do anyone can help?
Which value is equivalent to 8.7% written as a decimal? A. 0.087 B. 0.87 C. 8.7 D. 87.0

Evaluate |–8| + |b| + a if a = 0 and b = 12.

A. -4
B. 4
C. 12
D. 20

Answers

Answer:

Step-by-step explanation:

abs(-8) = 8

abs(12) = 12

8 + 12 = 20

D

A is the correct awnser

Choose an equation of a line through the point (-4, 1) perpendicular to y=−12x+3.

Answers

Answer:

y = (1)/(12)x + (4)/(3)

Step-by-step explanation:

slope of perpendicular line: m = (1)/(12)

solve for b:

1 = (1)/(12)(-4) + b

solve parenthesis:

1 = -(1)/(3)+b

add (1)/(3) to both sides:

b = (4)/(3)

final equation: y = (1)/(12)x + (4)/(3)

distribution of expenses for sales of 240,000 ace manufacturing company how many dollars were spent for operating expenses

Answers

labor cost = 240000 *0.4 = 96000

Solve for pi please.

Answers

Answer:

2A / r^2 = pi

Step-by-step explanation:

A = 1/2 pi r^2

Multiply by 2

2A = pi r^2

Divide by r^2

2A / r^2 =  pi r^2/r^2

2A / r^2 = pi

Rewrite the sum of 12 and 8 as a product of the LCM of the two numbers and another sum.​

Answers

Answer:

2 or 4

Step-by-step explanation:

What is y = (x-6)^2 - 2 in y = ax^2+bx+c form

Answers

easy, just expand
y=(x-6)^2-2
y=(x-6)(x-6)-2
y=x^2-6x-6x+36-2
y=x^2-12x+34
y=ax^2+bx+c
a=1
b=-12
c=34
y = (x - 6)² - 2
y = (x - 6)(x - 6) - 2
y = (x(x - 6) - 6(x - 6)) - 2
y = (x(x) - x(6) - 6(x) + 6(6)) - 2
y = (x² - 6x - 6x + 36) - 2
y = (x² - 12x + 36) - 2
y = x² - 12x + 36 - 2
y = x² - 12x + 34